Analysis on the Cognitive Impact of Social Mobile Games on Left-Behind Children in the Era of Big Data - Li, Mengyu; Li, Jinglei; Yasin, Megat Al Imran; Osman, Mohd Nizam; Hashim, Norliana Binti; Ang, Lay Hoon; Xue, Yitian (Frontiers in Public Health, 2022)
The popularity of mobile gaming has become a common sight in rural areas, and the problem of marginalized children’s mobile gaming has become the biggest challenge faced by rural education, and has become a hot topic in the education sector and society. The stage of marginalized children is the golden period of learning and growth. However, this stage is also the period when the marginalized children have the greatest fluctuations in their ideology due to various factors such as guardians and youth. With the development of big data, it has been applied to various aspects of people’s life. This article is based on qualitative research, with the interview method and observation method as the main method, supplemented by a questionnaire survey method. In the empirical analysis part, this article has a certain degree of expansion in data selection and research methods. The data selection adopts the data collected by the National Family Tracking Survey (CFPS) in 2018 and 2019 across the country. Compared with previous studies, we increased the scale of the research data, making the research results more meaningful. In the research method, the ordinary least squares method (OLS), the propensity score matching method (PSM) and the two-stage least square method (2SLS) are used, and multiple control variables are selected. The factor analysis of the original scores of the math test and the original scores of the word test is carried out to obtain the factor scores of cognitive ability. The emotion of the child is expressed by the depression score, and factor analysis is also performed on the depression score. Cognitive abilities refer to reasoning or thinking, processing speeds, and one’s ability to solve problems in novel situations, independent of acquired knowledge. OLS regression results show that left-behind children are worse than rural children in cognitive ability, and compared with rural children, left-behind children are more likely to be emotionally depressed.And whether they are accompanied by migration or rural children, there is no significant difference in their cognitive ability and emotions.